Enhancing intellectual capital for e-service innovation. Issue 1 (2nd January 2016) - Tsou, Hung-Tai; Chen, Ja-Shen; Liao, Shih-Wen (Jolie)
Abstract : The emergence of the knowledge-based economy has made intellectual capital a critical factor in assisting companies to obtain a competitive advantage in this fierce environment. This study adopted the knowledge-based view and resource-based view to explore and propose the influence of intellectual capital on e-service innovation and further examines the mediating effects of cross-functional integration and external collaborative competency on the relationship between intellectual capital and e-service innovation. An empirical study was performed based on a survey of information technology (IT) and marketing managers from financial and hotel industries in Taiwan. There were 126 companies whose two departments both responded to the questionnaires. The findings indicated that intellectual capital can promote the ability of firms to develop e-service innovation. Furthermore, cross-functional integration played a mediating role between intellectual capital and e-service innovation. This study suggested that managers should enhance intellectual capital in developing e-service innovation through cross-functional integration.